Correlation between body mass index and in-hospital mortality in patients with ST-segment elevation myocardial infarction in Erbil city- Iraq - Ahmed Abdullah , Azad; Naser Zangana, Salam (Diyala Journal of Medicine, 2021)
Background: Although High body mass index is associated with many cardiovascular diseases including coronary artery disease. Its effect on in-hospital death in patients with acute ST-segment elevation myocardial infarction (STEMI) is still a subject of controversy. Objective: To determine the correlation between body mass index (BMI) and in-hospital mortality in those patients. Patients and Methods: In this cross-sectional study, 180 adult patients with acute STEMI were enrolled and their BMI was measured. The participants were classified according to BMI into three groups as normal, overweight, and obese. A correlation between in-hospital mortality due to STEMI and BMI was evaluated. Results: Of the total participants, 62 (34.4%) were normally weighted, 61(33.8%) were over-weighted, and 57(31.6%) were obese. There was a significant difference (p= <0.001) between the groups concerning troponin I, hs-CRP, GRACE score, and the probability of in-hospital death. There were 16 (8.8%) in-hospital deaths during the study distributed as follows; 1(1.6%) in the normal-weight group, 5(8.1%) in the overweight group, and 10 (17.5%) in the obese group. In-hospital death showed a significant difference (p=0.04) between the study groups. In addition, a significant positive correlation(r=0.9) was found between BMI and in-hospital death. Conclusion: A robust positive correlation was detected between BMI and in-hospital mortality due to acute STEMI. When BMI increases, the number of deaths also increases exponentially.